2019
DOI: 10.3390/jcm8030289
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between a Weighted Multi-Gene Algorithm and Blood Pressure Control in Hypertension

Abstract: Hypertension (HTN) is a complex disease with interactions among multiple organ systems, including the heart, vasculature, and kidney with a strong heritable component. Despite the multifactorial nature of HTN, no clinical guidelines utilize a multi-gene approach to guide blood pressure (BP) therapy. Non-smokers with a family history of HTN were included in the analysis (n = 384; age = 61.0 ± 0.9, 11% non-white). A total of 17 functional genotypes were weighted according to the previous effect size in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…EH is a complex and polygene genetic disease, evidence suggests that polymorphism of gene has been associated with EH in various populations. [ 19 23 ] Our study provides a China-Russia biracial view of hypertension in the same geographical region for the first time. Our main findings were that…”
Section: Discussionmentioning
confidence: 98%
“…EH is a complex and polygene genetic disease, evidence suggests that polymorphism of gene has been associated with EH in various populations. [ 19 23 ] Our study provides a China-Russia biracial view of hypertension in the same geographical region for the first time. Our main findings were that…”
Section: Discussionmentioning
confidence: 98%
“…The NCT02524873 trial examined the genes involved in the pathogenesis of EH in adults. This study showed the interplay between gene polymorphisms and the correspondence to pharmacological therapy [90]. The MDR1 gene polymorphism does not decrease losartan concentration in plasma but offers a greater reduction in BP compared with the presence of the polymorphism [91].…”
Section: Clinical Trials Developed Evaluating the Pharmacological Cor...mentioning
confidence: 99%
“…This is particularly important in hypertension given the number of genes that are known to be associated with BP. Moreover, until whole genome sequencing and clinician understanding of whole genome sequencing is widespread, there needs to be transparent criteria for the genotypes selected that include allelic frequency (common and generalizable) and effect size (clinically meaningful) [11].…”
mentioning
confidence: 99%